Improvement Of Hybrid Digital Image Watermarking Schemes Based On Svd In Wavelet Transform Domain - Mohamed Hassan Makbol, Nasrin (2015)

(untitled)
Digital image watermarking techniques have enabled imperceptible information in images to be hidden to ensure the information can be extracted later from those images. Robustness, imperceptibility, capacity and security are the most important requirements of any watermarking scheme. Recently, hybrid Singular Value Decomposition (SVD)- based watermarking schemes in the wavelet domain have significantly gained a lot of attention. The aim of this study is to develop hybrid digital image watermarking schemes by combining the properties of SVD and the chosen wavelet transforms to achieve high robustness and imperceptibility, as well as maintaining the trade-off between robustness, imperceptibility and capacity. The security issue due to the false positive problem (FPP) that may be occurring in most of SVD-based watermarking schemes, has been covered and addressed. This study proposes five hybrid robust SVD-based image watermarking schemes in the wavelet domain. In the first scheme, a grey image watermark is embedded directly into the singular values (S) of each redundant discrete wavelet transform transform (RDWT) sub-band of the host image. The scheme is named RDWT-SVD. The second proposed scheme, namely IWT-SVD-AT, utilised the integer wavelet transform (IWT) instead of RDWT due to its properties. The watermark is scrambled using Arnold Transform (AT) before being embedded into the S of each IWT sub-band host. Despite the impressive results by the first and the second schemes, they were vulnerable to the FPP. Thus, they have failed to resolve the rightful ownership. In the third scheme, a hybrid IWT-SVD scheme is proposed with a novel Digital Signature (DS)-based authentication mechanism to solve the FPP. The scheme outperforms the previous schemes in terms of robustness, capacity, security, computation time and attains high imperceptibility. In the remaining two proposed schemes; the fourth and fifth schemes, the FPP is totally avoided using new different embedding strategies. In the fourth scheme namely IWT-SVD-MOACO, the singular vector U of the watermark is embedded into the S of IWT LL sub-band. Multi-objective ant colony optimisation (MOACO) is used to find the optimal multiple zooming/scaling factor (MZF) instead of the single scaling factor (SSF) to achieve the optimal trade-off between imperceptibility and robustness. Finally, a hybrid SVD block-based scheme namely DWT-SVD-HVS using discrete wavelet transform (DWT) is developed. A binary watermark is embedded into a number of blocks which is selected based on some human visual system (HVS) criterion. The scheme shows a high imperceptibility and good robustness. Finally, all the proposed schemes are evaluated with different colour images and had been shown a successful applicability with colour images.